2019
DOI: 10.1136/jech-2018-212010
|View full text |Cite
|
Sign up to set email alerts
|

Early-life inequalities and biological ageing: a multisystem Biological Health Score approach inUnderstandingSociety

Abstract: Social position is known to play a role in the quality of ageing, notably through the stimulation/dysregulation of key physiological systems in response to external stresses. Using data from one wave of Understanding Society including 9088 participants, we defined, as an extension of the allostatic load, a synthetic Biological Health Score (BHS) capturing the wear-and-tear of four physiological systems (endocrine, inflammatory, cardiovascular and metabolic systems) and two organs (liver and kidney). We used 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…We focus on a set of six biomarkers which were available in both surveys and are commonly accepted as biomarkers of healthy and functional ageing and predictors of chronic disease morbidity and mortality 16 . Social disparities in the selected biomarkers are often analysed in order to unpack the social to biological processes leading to health inequalities 21 . We analyse data from older adults aged 50 or over as this when many chronic diseases emerge.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on a set of six biomarkers which were available in both surveys and are commonly accepted as biomarkers of healthy and functional ageing and predictors of chronic disease morbidity and mortality 16 . Social disparities in the selected biomarkers are often analysed in order to unpack the social to biological processes leading to health inequalities 21 . We analyse data from older adults aged 50 or over as this when many chronic diseases emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Early adulthood Young adults with disadvantaged social characteristics already show a higher biological risk when compared to their more advantaged counterparts (46) and this is likely to track forwards. This biological risk is accelerated by unhealthy behaviors and living in deprived neighborhoods is associated with differences in risks for health across the lifecourse, including hazardous lifestyle factors from childhood and adolescence onwards, and worse glucose metabolism from early adulthood.…”
Section: The Right Interventions At the Right Time And On The Right Vmentioning
confidence: 99%
“…In order to further investigate the timing of social embodiment, we used data from Understanding Society (9,088 participants aged 20-80 years old), on 16 blood derived biomarkers capturing 6 physiological systems (including cardiovascular, inflammation, metabolic, endocrine systems and the functions of both liver and kidney). We (i) defined the Biological Health Score (BHS) as an extension of the AL incorporating two additional systems, (ii) investigated potential social gradients in BHS, (iii) explored the relative contribution of each physiological system to the BHS, and (iv) explored potential age differentials in BHS (46).…”
Section: Using Synthetic Scores In Lifepathmentioning
confidence: 99%
“…We considered as potential confounders the following variables previously used when analysing the BHS [11]:…”
Section: Socioeconomic Position and Covariatesmentioning
confidence: 99%
“…As an extension of the allostatic load, we previously developed a Biological Health Score (BHS) which included physiological systems not directly related to the stress response [11] , and showed that participants with lower educational attainment had higher BHS values (i.e. higher biological risk) independently of socially patterned exposures and behaviours.…”
Section: Introductionmentioning
confidence: 99%